Réponses

2013-03-31T15:52:19+02:00

46 : f(x) = x^3 - 1/x                         Df : R*

f'(x) = 3x² + 1/x²                              Df' : R*

 

47 : f(x) = 2x + Vx                          Df : ]0;+l'infini[

f'(x) = 2 + 1/(2Vx)                          Df' : ]0;+l'infini[

 

48 : f(x) = 3x² - x/2 + 4/5              Df : R

f'(x) = 6x - 1/2                                Df' : R

 

49 :  f(x) = x/3 - 3/x                       Df : R*

f'(x) = 1/3 + 3/x²                            Df' : R*

 

50 : f(x) = 3/(2x)                           Df : R*

f'(x) = -6/(4x²)                               Df : R*

 

51 : f(x) = V(4x/9)                       Df : ]0;+l'infini[

f'(x) = 1/(2V(4x/9)) * 36/81        Df' : ]0;+l'infini[

= 2/(9V(4x/9))

 

52 : f(x) = (x²+1) Vx                     Df : ]0;+l'infini[

f'(x) = 2xVx + (1/(2Vx)) (x²+1)     Df' : ]0;+l'infini[

= 2xVx + (x²+1)/(2Vx)

 

Pour le reste, il te suffit d'utiliser les formule suivante :

(u * v)' = u'v + v'u

(u+v)' = u' + v'

(u/v)' = (u'v - v'u) / v²